Outcome after new generation single-layer polytetrafluoroethylene-covered stent implantation for the treatment of coronary artery perforation - Kufner, Sebastian; Schacher, Nora; Ferenc, Miroslaw; Schlundt, Christian; Hoppmann, Petra; Abdel-Wahab, Mohamed; Mayer, Katharina; Fusaro, Massimiliano; Byrne, Robert A.; Kastrati, Adnan (Catheterization and Cardiovascular Interventions, 2019)
Aims: Coronary artery perforation (CAP) is a rare but severe complication during percutaneous coronary intervention (PCI). Implantation of covered stents (CS) represents a potentially life-saving treatment. Concerns exist regarding limited efficacy and high stent thrombosis (ST) rates related to early generation CS. The aim of this study was to evaluate angiographic and clinical outcomes of patients with CAP treated with a new generation single-layer polytetrafluoroethylene (PTFE)-CS. Methods: Between May 2013 and November 2017, we identified a total of 61 patients who underwent implantation of 71 single layer PTFE-CS after CAP. We analyzed angiographic results at follow up (including binary angiographic restenosis [BAR] and late-lumen-loss [LLL]) and clinical outcomes in hospital and at follow up, including target lesion revascularization (TLR), cardiovascular-, and all-cause mortality, myocardial infarction (MI) and stent thrombosis (ST). Results: Procedural success was achieved in all but two patients (96.7%). Procedure related MI, occurred in 19 cases (31.1%), in hospital death occurred in five cases (8.2%). At follow-up, TLR occurred in 11 cases (18.0%), two patients (3.3%) died from non-cardiovascular cause, there was no case of MI or ST. Conclusions: In this retrospective analysis, implantation of a new generation PTFE-CS, for the treatment of CAP showed high technical success rates. Although, periprocedural MI—and in-hospital-death rates remain not inconsiderable, new generation PTFE-CS showed favorable angiographic and clinical efficacy and high safety profile, especially with regard to thrombotic events.
CRIS-Team Scopus Importer:2019-05-02
Keywords: coronary artery perforation; covered stent